Thyroid Diseases and Intestinal Microbiome - Legakis, Ioannis; Chrousos, George P.; Chatzipanagiotou, Stylianos (Hormone and Metabolic Research, 2023)
The human microbiome plays an integral role in health. In particular, it is important for the development, differentiation, and maturation of the immune system, 70% of which resides in the intestinal mucosa. Microbiome studies conducted to date have revealed an association between disturbances in the microbiota (dysbiosis) and various pathological disorders, including changes in host immune status. Autoimmune thyroid diseases are one of the most common organ-specific autoimmune disorders, with a worldwide prevalence higher than 5%. The predominant autoimmune thyroid diseases are Hashimoto’s thyroiditis and Grave’s disease. Several factors, such as genetic and environmental ones, have been studied. In accordance with recent studies, it is assumed that the gut microbiome might play a significant role in triggering autoimmune diseases of the thyroid gland. However, the exact etiology has not yet been elucidated. The present review aims to describe the work carried out so far regarding the role of gut microflora in the pathogenesis of autoimmune thyroid diseases and its involvement in the appearance of benign nodules and papillary thyroid cancer. It appears that future work is needed to elucidate more precisely the mechanism for gut microbiota involvement in the development of autoimmune thyroid diseases.
Keywords: microbiome; thyroid diseases; autoimmunity; papillary thyroid cancer